Diuble Station Observation of Telescopic Meteors in Mykolaiv - Kulichenko, M.O. (Nauka ta Innovacii, 2017)
Meteor research using TV CCD unintensified techniques was started in 2011 in Nikolaev astronomical observatory (RI «NAO»). The method of meteor registration is based on the combined observation method developed at RI «NAO». The main accent of the research is made on the precise astrometry and meteoroid orbits calculation. In 2013 first double station meteors with low baseline were observed. Estimation of uncertainties of visible radiant equatorial coordinates, geocentric velocity and heliocentric meteoroid orbit parameters was carried out.